Effects of TikTok Content Marketing, Perceived Value, and Trust on Purchase and Repurchase Decisions in an Online Travel Platform - Alyana Isti Hasnani; Mochammad Tutuk Safirin (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The rapid growth of online travel agencies (OTAs) has intensified competition, requiring companies to understand the factors influencing consumers' purchase and repurchase decisions. This study aims to examine the effects of TikTok content marketing, perceived value, and trust on purchase decisions and repurchase decisions among online travel consumers in Surabaya. A quantitative approach was employed using a structured questionnaire distributed to 120 respondents selected through purposive sampling. The data were analyzed using Covariance-Based Structural Equation Modeling (CB-SEM) with AMOS. The results indicate that TikTok content marketing, perceived value, and trust have positive and significant effects on purchase decisions. Regarding repurchase decisions, perceived value has a positive and significant effect, whereas TikTok content marketing and trust do not have significant effects. In addition, purchase decisions significantly and positively influence repurchase decisions, confirming their important role in encouraging repeat purchases. Among the examined variables, perceived value is the strongest determinant of repurchase decisions. These findings suggest that online travel service providers should prioritize delivering superior value while maintaining effective TikTok marketing strategies and consumer trust to strengthen purchase and repurchase decisions. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation and Infrastructure